Evaluation of Microglial Activation in Multiple Sclerosis Patients Using Positron Emission Tomography - Airas, Laura; Nylund, Marjo; Rissanen, Eero (Frontiers in Neurology, 2018)
Understanding the mechanisms underlying progression in multiple sclerosis (MS) is one of the key elements contributing to the identification of appropriate therapeutic targets for this under-managed condition. In addition to plaque-related focal inflammatory pathology typical for relapsing remitting MS there are, in progressive MS, widespread diffuse alterations in brain areas outside the focal lesions. This diffuse pathology is tightly related to microglial activation and is co-localized with signs of neurodegeneration. Microglia are brain resident cells of the innate immune system and overactivation of microglia is associated with several neurodegenerative diseases. Understanding the role of microglial activation in relation to developing neurodegeneration and disease progression may provide a key to developing therapies to target progressive MS. 18 kDa translocator protein (TSPO) is a mitochondrial molecule upregulated in microglia upon their activation. Positron emission tomography (PET) imaging using TSPO-binding radioligands provides a method to assess microglial activation in patients in vivo. In this mini-review, we summarize the current status of TSPO imaging in the field of MS. In addition, the review discusses new insights into the potential use of this method in treatment trials and in clinical assessment of progressive MS.